The Influence of Service Quality to Customer Loyalty Through Customer Satisfaction and Brand Image - Mohammad Rifai Afif; Dewi Tamara; Yasin Irwanuddin; Hermawan Pramunaryo (Ridwan Institute, 2021)
This study shows whether service quality affects customer loyalty, brand image, and satisfaction as intervening variables. The service quality is very important to understand the satisfaction of customer to company’s product and services. The good and effective service quality is a combination of effective marketing strategy on retaining the customer and attract new customers. The customer loyalty in construction company is not easy to achieve due to special and customed expertise needed by each customer. The brand image in construction industry is not easy to achieve as in retail industry. The researcher used the quantitative method using survey or questionnaires. The researcher dispatched 300 surveys, but the returned is only 193, where the sample was the customers of PT Wijaya Karya Beton, Tbk. This paper utilizes Pearson's correlation and multiple linear regressions. The researcher also used hierarchical regression to assess the role of intervening. Indeed, the research result shows a significant relationship among purposed variables